Dothistroma needle blight, weather and possible climatic triggers for the disease's recent emergence. Issue 5 (29th January 2016) - Woods, A. J.; Martín‐García, J.; Bulman, L.; Vasconcelos, M. W.; Boberg, J.; La Porta, N.; Peredo, H.; Vergara, G.; Ahumada, R.; Brown, A.; Diez, J. J.
Summary: Dothistroma needle blight (DNB), caused by the two fungi Dothistroma septosporum and D. pini, is a major disease of pines with a worldwide distribution. Increases in the incidence and severity of disease in areas where the disease has long been established and notable range expansions have both recently been observed. The aim of this review was to assess the relationship between DNB, weather factors and climate to better understand possible underlying causes of this recent intensification in disease. A substantial body of literature shows that the life cycles of the fungi are closely related to weather factors such as precipitation and temperature. Given the rapid response of DNB to favourable weather conditions, it seems plausible that changes in disease behaviour could be due to changes in climate. The recurrent El Niño‐Southern oscillation (ENSO) phenomenon influences patterns of temperature and precipitation in many regions of the world, often resulting in warmer and wetter conditions than normal. We found that since the 1950s, four of the past five strong El Niño events appear to have coincided with reports of increased DNB activity on an intercontinental scale. The lack of long‐term standardized data records limits our ability to fully interpret this relationship, but the projected future climatic conditions in the Northern Hemisphere appear to be increasingly favourable for the disease. Still, other areas of the world may become less favourable, and further research is required to be able to accurately predict DNB outbreaks and their impact on pine forests in the future.